Sperm guidance in mammals - An unpaved road to the egg - Eisenbach, Michael (2006)
Contrary to the prevalent view, there seems to be no competition in the mammalian female genital tract among large numbers of sperm cells that are racing towards the egg. Instead, small numbers of the ejaculated sperm cells enter the Fallopian tube, and these few must be guided to make the remaining long, obstructed way to the egg. Here, we review the mechanisms by which mammalian sperm cells are guided to the egg.